Predicting difficulty in laparoscopic cholecystectomy preoperatively using a scoring system - Raza, Mohammed; M., Venkata Rajeev (International Surgery Journal, 2019)
Background: Laparoscopic cholecystectomy (LC), one of the most commonly performed surgical procedures worldwide. Preoperative assessment of difficulty is needed for frequent procedures such as LC in order to avoid complications, preparedness and to guarantee an efficient course of surgery. But there is no scoring system available to predict the difficulty preoperatively. Methods: In our study we have tried to predict a difficult LC preoperatively using a modified scoring system proposed by Randhawa et al. Patients diagnosed to have GB stones requiring LC were evaluated with following factors age, gender, duration of illness, h/o previous GB disease, underwent ERCP, BMI, abdominal scar whether infra umbilical or supraumbilical, palpable gallbladder, sonographic findings - gall bladder wall thickness, pericholecystic collection, impacted stone. Various clinical and radiological and intra-operative parameters were scored. Procedure is graded based on individual surgeon’s opinion as easy/difficult/very difficult. The parameters were analyzed to find their correlation to predicting difficult LC. Degree of difficulty was analyzed. Results: Preoperative scoring system proposed by Randhawa et al that we modified was found to be appropriate for predicting operative outcome in LC, having overall p value for the scoring system of <0.001, with sensitivity of 90.9, specificity of 73.1% and area under RoC of 0.876. In present study, palpable gall bladder, history of previous cholecystitis, and the radiological parameters i.e. GB wall thickness, pericholecystic fluid and impacted stone to be statistically significant. Conclusions: Present modified Randhawa and Pujahari scoring system is valuable and appropriate for predicting operative outcome in laparoscopic cholecystectomy. This, in turn, facilitates better preparedness.